ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN JAM TANGAN SWISS ARMY (Studi Kasus pada Konsumen Swiss Army di Adam Watch) - Ashar, Muhammad Ravi; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2018)
This research was motivated by the intense competition in the Indonesian wristwatch industry with the emergence of various new brands in the market. This is impacting (affect) on sales of Swiss Army watches that far adrift than its competitors. This study aimed to test the effect (influence) of brand equity elements which consist of brand awareness, perceived quality, brand associations and brand loyalty of purchase decision on the Swiss Army watches.The samples in this studi were 100 respondets who buy Swiss Army watches, repair or replace Swiss Army watches battery, and come to the store using Swiss Army watches. The method used was purposive sampling ato spread questionnaries to the respondents. This study uses a quantitative analysis method, namely validity and reliability, the classic assumption test, linier regression analysis and the tesh the feasibility of the model.The data that have subjected the test of validity, reliability test and classical assumption test processed using SPSS (Statistical Package for Social Science) for Windows 7.Where the buying decision variable (Y), brand awareness (X1), perceived quality (X2), brand association (X3), and brand loyalty (X4). Hyothesis testing using t test showed that the three variables of brand awareness, perceived quality, brand associations has a significant positive effect to purchasing decision. Meanwhile, one other independent variables, brand loyalty have positive and not significant effect to purchasing decision. F test reveal that all independent variables are adequate to test dependent variable purchasing decision. Adjusted R Square of 0,425 shows that 42,5 percent of purchasing decision variation can be explained by four independent variables in the regression equation. While the rest 57,5 percent is explaindes by ither variables outside of the four variables used in this study.